Investigation of the Performance of Esports Games with Data Envelopment Analysis - Güral, Y.; Gürcan, M.; Devecioğlu, S.; Halisdemir, T.A. (Universidad de Murcia Servicio de Publicaciones, 2022)
Today, electronic sports tournaments such as the World Cyber Game, European Nations Championship, International Premiership Series and Esl Pro Series are organized. These tournaments include popular games such as CounterStrike, Dota 2, League of Legends, StarCraft 2, Super Smash Bros and Street Fighter. In this study, the performances of eSports games will be analyzed with Data Envelopment Analysis (DEA). Accordingly, it is aimed to help eSports companies to be effective by determining the relative efficiencies of eSport games, effective and ineffective DecisionMaking Units (DMUs production units that produce similar outputs using similar inputs). For this purpose, determining the effective games and comparing the other games according to them enables the optimization of the values of the output variables according to the input variable. DEA is a non-parametric method used to study the relative effectiveness of Decision Making Units when there are multiple inputs and multiple outputs. Data Envelopment Analysis (DEA) is a non-parametric method used to examine the relative efficiency of Decision Making Units (DMUs production units that produce similar outputs using similar inputs) when there are multiple inputs and multiple outputs. Measuring the efficiency of businesses and knowing the source of their inefficiency is an important issue for eSports as in every sector. Data Envelopment Analysis is frequently used for measuring the efficiency of DMU. In this study, efficiency analysis was performed by taking into consideration the 27 games in the first 200 games on the e-charts website in 2018. With this analysis, the efficiencies and changes of efficiencies of the games in 2018 were tried to be obtained. According to the results of the research: Counter-Strike and Minecraft were determined to be effective games. Since the other 25 games are inefficient, target values for these games are given in the study © 2022. Servicio de Publicaciones de la Universidad de Murcia. All Rights Reserved.
Investigação do Desempenho dos Jogos Esports com Análise de Envelopamento de Dados]; [Investigación del Rendimiento de los Juegos de Esports con Análisis Envolvente de Datos
Keywords: DEA; DEA; DEA; Digital Games; Efficiency; Eficiencia; eficiência; eSportes; eSports; eSports; Jogos digitais; Juegos digitales